Cambodian Simplicia (Plumeria sp.) Phytochemical Screening Study: A Systematic Literature Review - Lia Fika Yuniar; Syalomita, Delika; Ismi Puji Apriani; Ira Puspawati; Zevania Toguria Nadeak; Khoirul Haniatin; Novita Andriyani; Mila Febriyanti (Eureka Herba Indonesia, 2023)
Plumeria phytochemical screening is important to understand the chemical composition of this plant and its potential in the pharmaceutical and health fields. Through phytochemical analysis, researchers can determine the dominant compounds in plants, study their mechanism of action, and evaluate their biological activity. Phytochemical screening can be carried out using sophisticated analytical methods such as chromatography, spectroscopy, and biological assays to deeply understand the phytochemical profile of Plumeria. This study aimed to carry out a systematic review to explore the phytochemical screening of Plumeria sp. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the evaluation of the phytochemical analysis of Plumeria sp. This study follows the preferred reporting items for systematic reviews and meta-Analysis (PRISMA) recommendations. The process of phytochemical screening was carried out qualitatively and quantitatively. Plumeria sp contains various alkaloids, flavonoids, terpenoids, and phenolic compounds.